PHYSICAL TRAINING AND ANTHROPOMETRIC AND CARDIORESPIRATORY ADJUSTMENTS (Fiep Bulletin - online, 2013)
Physical training is a systematic and progressive method, with the application of specific exercises, which seeks to improve people's anthropometric profile and cardiorespiratory capacity. The study focuses on the application of reliable tests in the functional evaluation, including the anthropometric and ergospirometric. It is proposed, therefore, to analyze the correlation between anthropometric variables and physiological and metabolic responses to exercise, of recruits and athletes, comparing the performance of these groups. Participated in this cross-sectional study 28 subjects, twenty recruits and eight athletes (six men), with a mean age of 18.35 (± 0.49) and 23.50 (± 6.76), respectively. Data collection consisted of anthropometric measurements that comprise body mass index (BMI), waist circumference (WC), waist/hip ratio (WHR) and body fat percentage (BF%). Additionally, it was applied the cardiopulmonary exercise test with Bruce protocol, conducted on a treadmill, using TEEM-100 gas analyzer, and observed the responses of oxygen consumption (VO2) and carbon dioxide production (VCO2), from which it was estimated the respiratory quotient (RQ). In the data analysis it was used the statistical package SPSS (18.0), through the mean, standard deviation, Student's t-test and Pearson's Correlation Test, with p
Keywords: energy metabolism; athletic performance; physical fitness